Educational Intervention on Self Care among Chronic Kidney Disease Patients Undergoing Haemodialysis in a Tertiary Hospital Of Kathmandu, Nepal - Sah, Bimala Kumari; Pandey, Apsara; Bhandari , Nisha; Luitel, Kopila; Dev , Renu (Tribhuvan University Journal, 2024)
Introduction: The burden of chronic kidney disease (CKD) is increasing globally, educational intervention to the CKD patients is crucial to self-manage the problems arising from disease and haemodialysis. The study aims to assess the effect of educational intervention on self-care among chronic kidney disease patients undergoing haemodialysis. Methods: The pre-experimental design was used for assessing the effect of educational intervention on self- care among CKD patients undergoing haemodialysis in Tribhuvan University Teaching Hospital. A total of 43 patients were included using nonprobability purposive sampling technique. Face to face interview with structured interview schedule was conducted for data collection followed by educational intervention with educational package to each individual. After 6 weeks of intervention, post-test was carried out with the same interview schedule to the same participants who were participated in pre-test and intervention. Both descriptive and inferential statistics were used for the interpretation of data. Inferential statistics- paired t- test was used to measure the significant difference on Knowledge score on Self-care before and after educational intervention. Results: The findings of the study showed significantly increased knowledge score after the intervention in diet (p=0.001), exercise (p=0.001), infection prevention (p=0.001), stress management (p=0.001), complication prevention (p=0.001), laboratory test (p=0.001) and total knowledge score (p=0.001) with 95.0% confidence level (p-value <0.05). However, in fistula care the score increased insignificantly (p-value: 0.250). Conclusions: Educational intervention increased the knowledge score, so it is obligatory to conduct the intervention program for improvement in self - care among chronic kidney disease patients undergoing haemodialysis. >